New species of Cymbella and Placoneis (Bacillariophyta) from late Pleistocene Fossil, China - Gong, Zhijun; Li, Yanling; Metzeltin, Ditmar; Lange-Bertalot, Horst (Phytotaxa, 2013)
This paper describes five new Cymbella, one new Cymbopleura and one new Placoneis species from the late Pleistocene of the Jianghan Plain in China, based on light–and scanning electron microscopy of valve morphology. The characteristic morphological features of the seven new species differ from known established taxa by valve shape, both the central portion and apices, length/breadth ratio, shape of the central area and presence or absence of stigmata. All six cymbelloid taxa are as yet found only in fossil deposits of the Jianghan Plain. The Placoneis species, however is apparently conspecific with an extant population observed in Northern Myanmar (Burma, Southeast Asia).